Implementasi Program Training Pegon Dalam Meningkatkan Kemampuan Membaca Dan Menulis Pegon Bagi Santri Di Pondok Pesantren Hidayatul Mubtadiin - Ummi Rohmiyati; Endang Ekowati; Ami Latifah (Departement of Mathematics Education, 2024)
The main objectives of this research are: 1) To find out how the process of implementing the Pegon Training Program is in improving Pegon's reading and writing skills at the Hidayatul Mubtadiin Islamic Boarding School, 2) To find out the supporting and inhibiting factors in the process of implementing the Pegon Training Program at the Hidayatul Mubtadiin Islamic Boarding School. The method used is qualitative with data collection techniques in the form of interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation (data display) and drawing conclusions (verification). Data examination was carried out using triangulation. The results of the research show that the implementation of the pegon training program has been carried out well and is quite effective, with the Ustadz teaching Arabic pegon writing by introducing hijaiyah letters in improving the quality of reading the yellow book by using various methods so that the students can receive and understand pegon The supporting factors for good implementation are Ustadz and Ustadzah who are patient and consistent, pegon guidebooks, enthusiasm and interest of the students, facilities and infrastructure. The inhibiting factors for the pegon training program are low enthusiasm and: students' feeling of laziness in learning which sometimes arises because they have never studied pegon, limited time and weakened enthusiasm.